ANALISIS PERSAMAAN DAN PERBEDAAN PELAFALAN DALAM BAHASA ACEH ANTARA DIALEK ACEH SELATAN DAN DIALEK ACEH UTARA - Rami Nurpita; Iba Harliyana; Safriandi Safriandi (Jurnal Dedikasi Pendidikan, 2021)
Abstract: This research is entitled “Analysis of the Similarities and Differences in Pronunciations of Acehnese in South Aceh and North Aceh Dialect”. This study aims to describe the similarities and differences in the pronunciation of North Aceh dialect and South Aceh dialect. The approach used in this study is aqualitative approach. The data was collected using the observation method with tapping technique followed by listening  proficiently, observing, taking notes, and recording. The data of this research are oral data in the form of words and sentences of Acehnese in the South Aceh dialect and the Nourth Aceh dialect. The data sourtces of this study were native speakers of Acehnese in South Aceh dialect and North Aceh dialect. The researchers selected two sub-districts in each district, namely North Kluet and Kota Bahagia sub district in South Aceh. Meanwhile, the two sub-districts in North Aceh were Muara Batu and Bandar Baro sub-district. The results of the data analysis found that there were pronunciation similaritien, but the meanings were differences in pronunciation similarities, but the meanings were different and there were differences in pronunciation, but the meaning was the same in the South Aceh dialect and the Nourth Aceh dialect.  Abstrak: Penelitian ini berjudul “Analisis Persamaan dan Perbedaan Pelafalan dalam Bahasa Aceh Dialek Aceh Selatan dan Dialek Aceh Utara”. Penelitian ini bertujuan untuk mendeskripsikan persamaan dan perbedaan pelafalan bahasa Aceh dialek Aceh Selatan dan dialek Aceh Utara. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Pengumpulan data menggunakan metode simak dengan teknik sadap yang diikuti teknik simak libat cakap, simak bebas libat cakap, catat, dan rekam. Data penelitian ini adalah data lisan berupa kata dan kalimat dialek bahasa Aceh Selatan dan dialek bahasa Aceh Utara. Sumber data penelitian ini adalah penutur asli bahasa Aceh dialek Aceh Selatan dan dialek Aceh Utara, peneliti memilih dua kecamatan di masing-masing kabupaten, yaitu Kecamatan Kluet Utara dan Kecamatan Kota Bahagia di Aceh Selatan; Kecamatan Muara Batu dan Kecamatan  Banda Baro di Aceh Utara. Hasil analisis data menemukan bahwa terdapat persamaan pelafalan, tetapi maknanya berbeda dan terdapat perbedaan pelafalan, tetapi maknanya sama pada dialek bahasa Aceh Selatan dan dialek bahasa Aceh Utara.